(untitled) (Research, Society and Development, 2020)
This article presents the results of a research carried out as a conclusion to the Biological Sciences Degree Course, offered by the Federal University of Rio de Janeiro - UFRJ. Its main goal is to analyze the teaching practice applied to Science Teaching in the Final Years of Elementary School, aiming to understand the importance that the discipline has for students of this type of teaching in the school environment and to identifying what are the resources currently used in the classroom by teachers, but also to present proposals for activities that streamline the Science Teaching process in a way that makes it more dynamic and enjoyable for students. The theoretical foundation that anchors this research is based on the studies of the following theorists: Saviani (2013), with his studies on traditional teaching pedagogies, Carvalho (2013), through his studies with the theory of SEIS - Investigative Teaching Sequences, Bizzo (2006), with his methodologies for Science Teaching, and Tardif (2014), through his studies on teaching practice. The applied methodology is based on a bibliographic review, which made it possible to understand the teaching practices with regard to Science Teaching in the Final Years and what resources are used in the classroom nowadays as well as the importance of the experimentation process as a support tool during classes. Thus, it can be seen that the experimentation process has an important role in learning, enriching the content addressed by teachers, making teaching and learning more dynamic, interactive and beneficial for the student.